2008
DOI: 10.1002/cncr.23293
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram predicting long‐term biochemical recurrence after radical prostatectomy

Abstract: BACKGROUND Men who undergo radical prostatectomy (RP) are at long‐term risk of biochemical recurrence (BCR). In this report, the authors have described a model capable of predicting BCR up to at least 15 years after RP that can adjust predictions according to the disease‐free interval. METHODS Cox regression was used to model the probability of BCR (a prostate‐specific antigen level >0.1 ng/mL and rising) in 601 men who underwent RP with a median follow‐up of 11.4 years. The statistical significance of nomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 31 publications
1
82
0
13
Order By: Relevance
“…Pathologic stage, Gleason score, and surgical margin status are independent predictors of biochemical recurrence and are used in nomograms to predict outcome (10). A recent meta-analysis has shown that GSTP1 hypermethylation may also be a potential predictive biomarker (11).…”
Section: Introductionmentioning
confidence: 99%
“…Pathologic stage, Gleason score, and surgical margin status are independent predictors of biochemical recurrence and are used in nomograms to predict outcome (10). A recent meta-analysis has shown that GSTP1 hypermethylation may also be a potential predictive biomarker (11).…”
Section: Introductionmentioning
confidence: 99%
“…Тем не менее, рецидив или прогрессирование заболевания после проведенных ради-кальных методов терапии наблюдается достаточно часто. Так, биохимический рецидив после хирургического лечения развивается у 27-53% больных [2][3][4][5]. Клиническая прогрес-сия заболевания в виде появления отдаленных метастазов имеет место только у трети больных с биохимическим ре-цидивом [6].…”
unclassified
“…According to the 2012 version of the clinical practice guidelines for prostate cancer in Japan (15), RP is recommended for patients who are not expected to develop PSA recurrence, such as those with a bGS ≤7, a PSA level of <10 ng/ml and a cT of cT1c-T2c. This guideline is based on the results of a variety of prognostic studies with large RP samples (16)(17)(18)(19), although these studies were retrospective. However, there is no definitive reason as to why RP is should not be used, even in high-risk cases of PSA recurrence (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%